Piezoelectric tuning fork biosensors for the quantitative measurement of biomolecular interactions. (17th November 2015) - Gonzalez, Laura; Rodrigues, Mafalda; Maria Benito, Angel; Pérez-García, Lluïsa; Puig-Vidal, Manel; Otero, Jorge
Abstract: The quantitative measurement of biomolecular interactions is of great interest in molecular biology. Atomic force microscopy (AFM) has proved its capacity to act as a biosensor and determine the affinity between biomolecules of interest. Nevertheless, the detection scheme presents certain limitations when it comes to developing a compact biosensor. Recently, piezoelectric quartz tuning forks (QTFs) have been used as laser-free detection sensors for AFM. However, only a few studies along these lines have considered soft biological samples, and even fewer constitute quantified molecular recognition experiments. Here, we demonstrate the capacity of QTF probes to perform specific interaction measurements between biotin–streptavidin complexes in buffer solution. We propose in this paper a variant of dynamic force spectroscopy based on representing adhesion energies E (aJ) against pulling rates v (nm s –1 ). Our results are compared with conventional AFM measurements and show the great potential of these sensors in molecular interaction studies.